Headache Characteristic in Covid-19 Infected Patient: A Systematic Review - Vina Lidya Setjaputra; Steven Christian Susianto; Abdulloh Machin (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: The neurotropism of COVID-19 virus has been addressed in several studies, and headache is one of the most frequent neurologic manifestations of COVID-19, with various results of characteristics and phenotype. In this systematic review, we aimed to characterize the most common phenotype of headache in COVID-19 infected patients. Methods: A systematic literature was conducted through Pubmed, SciElo and Cochrane databases with keywords (headache[Title]) AND (covid-19[Title]), ((neurological) AND (headache) AND (characteristic)) AND (covid-19), ((phenotype) AND (headache)) AND (covid-19). We extracted the study design, demographics of subjects, and characteristics of headache (onset, site, lateralization, quality, intensity, and additional symptoms related to headache). Results: We included 1381 subjects with COVID-19 infection who experienced headache symptoms from eligible 9 studies. The majority of our patients had headaches that occurred with COVID-19 symptoms onset (94.2%), ranging from 1 to 10 days after the first COVID-19 symptoms. The most common headache site was frontal (42.3%), followed by diffuse/ holocranial (40.1%), periorbital/retroorbital (24.2%), and temporal (23.8%), with no lateralization/occurring bilaterally (85.9%), and pain characteristic predominantly pressing and tightening (55.9%), throbbing (25.3%), and stabbing (9.8%). Headache intensity measured by VAS score ranged mild to moderate in most cases with duration mostly 1-24 h. 57% of headache patients were also accompanied by fever symptoms. Additional headache symptoms were also recorded, predominantly anosmia/ageusia, followed by photophobia/phonophobia, and nausea/vomiting. Conclusion: Bilateral, long-lasting, with pressing-tightening characteristic headaches accompanied by fever, were more frequent in COVID-19 infected patients, in conjunction with anosmia/ageusia. These features may help physician to determine the headache related to COVID-19.